The Complete Chloroplast Genome Sequence of Melilotoides ruthenica: Structural Comparative and Phylogenetic Analysis in Leguminosae. Issue 1 (March 2021) - Yan, Weihong; Shi, Wengui; Tian, Qingsong; Li, Zhiyong; Gao, Haijuan
Abstract: Melilotoides ruthenica is used for herbage with high nutrition and anti-drought. Complete chloroplast genomes are employed for the relationship analysis of phylogeny within plant families. High-throughput sequencing technology was used to exhibit the sequence of complete chloroplast of M. ruthenica . The genome is constituted by a circular molecule (130, 149 base pairs (bp)) which contained only one copy of inverted repeat sequence. The genome encodes 116 genes, including 85 protein-coding genes (73.28%), 26 tRNA genes (22.41%), and 5 rRNA genes (4.31%), respectively. 113 genes are single copy and 3 genes (psaA, ndhK, and ccsA) have double copies that are duplicated in the cp genome. The coding capacity of protein-coding genes of totally 17, 455 codons was represented in the M. ruthenica cp genome. Among these codons, 776 encoding for isoleucine and 48 for cysteine are the most and the least amino acids, respectively. The M. ruthenica cp genome has 12 intron-containing genes and the gene rps12 is trans-splicing in the cp genome. High codon usage was observed for phenylalanine and leucine. Phylogenetic analysis demonstrated that M. ruthenica and Medicago truncatula have close relationship with Vicia Sativa, Lens Calinaris and Lathyrus Tingitanus . Our results help to develop the chloroplast molecular biology and provide data information for the study of genetic breeding of M. ruthenica .